Magnetic Switching by the In Situ Electrochemical Control of Quasi‐Spin‐Peierls Singlet States in a Three‐Dimensional Spin Lattice Incorporating TTF‐TCNQ Salts. Issue 17 (15th February 2018) - Fukunaga, Hiroki; Tonouchi, Masanori; Taniguchi, Kouji; Kosaka, Wataru; Kimura, Shojiro; Miyasaka, Hitoshi
Abstract: Magnetic phase switching in a coordination polymer is reported, which is demonstrated by combining two processes: (A) the pre‐organization of magnetic/redox‐active molecules into a framework, and (B) a post‐treatment through electrochemical tuning of the pre‐organized molecules. A TTF .+ –TCNQ .− salt (TTF=tetrathiafulvalene; TCNQ=7, 7, 8, 8‐tetracyano‐ p ‐quinodimethane) was incorporated into a three‐dimensional framework with paddlewheel‐type dimetal(II, II) units ([ M 2 II, II ]; M =Ru with S= 1, 1 ; and Rh with S= 0, 2 ), where the [ M 2 II, II ] and TCNQ .− units form the coordinating framework, and TTF .+ is located in the pores of framework, forming an irregular π‐stacking alternating column with the TCNQ .− in the framework. In1, the spins of [Ru2 II, II ] and TCNQ .− units make a magnetic correlation through the framework upon decreasing the temperature from 300 K, which is, however, suddenly suppressed below 137 K (= T d (1 )) by the formation of a spin singlet in the TTF .+ –TCNQ .− columns, as seen in the spin‐Peierls transition ( T d (2 )=200 K). This material was incorporated as a cathode in a Li‐ion battery (LIB); a long‐range ferrimagnetic correlation was formed through the three‐dimensional [Ru2 II, II 2 TCNQ] − framework at T c =78 K in the discharge process. The reversible magnetic phase switching between the non‐volatile ferrimagnetic and paramagnetic states, resulting from the local spin tuning of quasi‐spin‐Peierls singlet, is demonstrated through the discharge/charge cycling of the LIB. Abstract : Switch and bait : Hiding a specific function of a material using a masking trigger (i.e., function inactivation) and then triggering the functionality by applying an external stimulus is a unique way to bring on‐demand functionality to a molecular system. Here the magnetic phase switching of a MOF compound, achieved by manipulating pre‐organized trigger molecules with a spin‐Peierls singlet state is demonstrated, followed by using an electrochemical post‐treatment for framework‐function activation at a precise point.